2021
DOI: 10.1186/s41043-021-00229-y
|View full text |Cite
|
Sign up to set email alerts
|

Salt intake was higher among males and those with high BMI and waist circumference: introduction to the Malaysian Community Salt Survey (MyCoSS), a population-based salt intake survey in Malaysia

Abstract: Background Recognising that excessive dietary salt intake is associated with high blood pressure and adverse cardiovascular health, the Ministry of Health Malaysia conducted the Malaysian Community Salt Survey (MyCoSS) among Malaysian adults. This paper introduced MyCoSS projects and presented findings on the salt intake of the Malaysian adult population. Methods MyCoSS was a nationally representative survey, designed to provide valuable data on di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Moreover, research done to investigate the relationship between urinary sodium and obesity indices found that greater urinary sodium excretion was associated with higher waist circumference besides other obesity markers ( 24 ). All the results confirmed the presence of a positive correlation between salt consumption and increasing waist circumference ( 22 – 24 ). Additionally, the present study showed an increase in the risk of poor glycemic control for patients, who were following a low-salt diet.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, research done to investigate the relationship between urinary sodium and obesity indices found that greater urinary sodium excretion was associated with higher waist circumference besides other obesity markers ( 24 ). All the results confirmed the presence of a positive correlation between salt consumption and increasing waist circumference ( 22 – 24 ). Additionally, the present study showed an increase in the risk of poor glycemic control for patients, who were following a low-salt diet.…”
Section: Discussionsupporting
confidence: 65%
“…According to a survey that was done in Malaysia on Malaysian citizens aged 18 and above, the authors showed that sodium intake was higher among male participants with a higher waist circumference ( 22 ). Another study conducted to estimate the relationship between sodium intake and obesity revealed that sodium consumption was significantly associated with a larger waist circumference and greater BMI ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…On average, women in this study exceeded the waist circumference recommendation of ≥80 cm, which was comparable with a previous local study, in which the women had a mean waist circumference of 88.6 cm (Ambak et al, 2021). An increased waist circumference (>80 cm for women) could indicate abdominal obesity or visceral adiposity (Després, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…Urine samples were obtained from approved project entitled "Populationbased Salt Intake Survey to Support the National Salt Reduction Programme for Malaysia (Malaysian Community Salt Study-MyCoSS)". Since this study is an extension of the MyCoSS study, study design, sample size, sample collection, study instrument and other related parameters adhered to the MyCoSS study (Ambak et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Only one participant was selected from a living quarter. If there were more than one eligible participant, selection was made using a modified Kish Table (Ambak et al 2021).…”
Section: Methodsmentioning
confidence: 99%